Analisis Performansi Turbin dan Generator di PLTP Lahendong Unit 1 Tomohon - La Ode Musa; Abdul Rahman; Ikral Gapshel; Triska Sombokanan (Jurnal Teknik Mesin Sinergi, 2019)
Lahendong Geothermal power plant is one of the Geothermal power plants in Indonesia which has four units and it be able to generate 4 × 20 MW of electrical energy by utilizing geothermal energy in the form of steam that supplied from wells created by Pertamina. The aim of this study is to determine the performance of the turbine and generator unit 1 which has been operated since 2001 by using thermodynamic analysis method calculating the steam quality and turbine work. Afterwards, turbine efficiency, turbine power and generator power were obtained. The average quality of geothermal steam at Lahendong in 2001 and 2015 were 0.8002 and 0.8065. Turbine’s performance decreased in 2001 (664.021 kJ / kg) until 2015 (640.799 kJ / kg), with the highest generator rotation tolerance of 0.9%.